Amplified excited state intramolecular proton transfer fluorescence of butterfly-shaped bis-2, 6-dibenzothiazolylphenol. (8th June 2017) - Zhang, Xuan; Ma, Wei-Wei
Abstract: A butterfly-shaped benzothiazole derivative, bis-2, 6-dibenzothiazolylphenol (2 ), was synthesized via 4-methylene bridging two 2, 6-dibenzothiazolylphenol (1 ) molecules, and the excited-state intramolecular proton transfer (ESIPT) fluorescence of1 and2 were comparably investigated by steady-state spectroscopic experiments with the aid of theoretical simulations for structure and energy. It was found that2 showed similar ESIPT emissions to those of1 in solution and solid states, but the ESIPT fluorescence quantum yield was substantially amplified in the case of the more 'integrated'2 . In both tetrahydrofuran (THF) and CHCl3 solvents, ESIPT occurred and orange emissions at 580–590 nm from keto tautomers were observed, where the absolute fluorescence quantum yield was measured to be 0.28 and 0.41 for1, as well as 0.41 and 0.59 for2, respectively. In the solid state, 2 showed an ESIPT emission at 570 nm with an absolute fluorescence quantum yield of 0.38, which is substantially shorter and larger than the corresponding values of1 (592 nm and 0.26) respectively. Furthermore, both2 and1 showed strongly blue-shifted green emissions around 520 nm from the deprotonated anion species in N, N-dimethyl formamide (DMF). A similar blue-shifted green emission was also found with the addition of fluoride in the THF solution of2 or1, suggesting that the competitive deprotonation makes the ESIPT impossible.